Growth reactions at the initial stages of the ontogenesis of white lupin with the use of growth-regulating compounds - Shitikova A.V.; Gataulina G.G.; Konstantinovich A.V. (BIO Web of Conferences)
The research was conducted in 2024 in a laboratory experiment at the Russian State Agrarian University - Moscow Timiryazev Agricultural Academy (Moscow). When studying the effect of short peptides on the sowing qualities of white lupine seeds, a negative effect on the energy of seed germination was found. The lowest values of germination energy were observed when using dipeptide KE at concentrations of 1*10-9 g/l and 1*10-12 g/l and amounted to 28% and 16%, respectively. The germination of white lupine seeds was noted at the maximum level and amounted to 100% when using all the studied concentrations. As for the treatment of seeds with tetrapeptide AEDG, there was also a decrease in the values of the germination energy of white lupine seeds at the level of 52% and 38% for concentrations of 1*10 -6 g/l and 1*10 -15 g/l compared with the control variant. Germination significantly differed from the control variant only when using tetrapeptide ARG at a concentration of 1*10 -6 g/l and was 88%.